Initialization of a methane-fueled single-chamber solid-oxide fuel cell with NiO + SDC anode and BSCF + SDC cathode - Zhang, C.; Zheng, Y.; Ran, R.; Shao, Zongping; Jin, W.; Xu, N.; Ahn, J. (Elsevier SA, 2008)
The initialization of an anode-supported single-chamber solid-oxide fuel cell, with NiO + Sm0.2Ce0.8O1.9 anode and Ba0.5Sr0.5Co0.8Fe0.2O3-d + Sm0.2Ce0.8O1.9 cathode, was investigated. The initialization process had significant impact on the observed performance of the fuel cell. The in situ reduction of the anode by a methane-air mixture failed. Although pure methane did reduce the nickel oxide, it also resulted in severe carbon coking over the anode and serious distortion of the fuel cell. In situ initialization by hydrogen led to simultaneous reduction of both the anode and cathode; however, the cell still delivered a maximum power density of ~350 mW cm-2, attributed to the re-formation of the BSCF phase under the methane-air atmosphere at high temperatures. The ex situ reduction method appeared to be the most promising. The activated fuel cell showed a peak power density of ~570 mW cm-2 at a furnace temperature of 600 °C, with the main polarization resistance contributed from the electrolyte. © 2008 Elsevier B.V. All rights reserved.